Transformation of Carbon Dioxide to Formic Acid and Methanol - Wang, Wan-Hui (SpringerBriefs in Green Chemistry for Sustainability,, 2018)
This brief explains the principles and fundamentals of carbon dioxide utilization and highlights the transformation to fuels and value-added chemicals such as formic acid and methanol. It is divided into six chapters, including an introduction to the basics of CO2 utilization and transformation of CO2 to formic acid and methanol with homogeneous and heterogeneous catalysts, respectively. The brief will appeal to a wide readership of academic and industrial researchers focusing on homogeneous and heterogeneous catalysis, organometallic chemistry, green chemistry, energy conversion and storage.